2016
DOI: 10.3233/wor-162288
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a Return-to-Work Coordinator model of care in a general hospital to facilitate return to work of injured workers

Abstract: The addition of a RTWC into the hospital model of care is effective in facilitating early RTW for injured workers. This could be a potential model of care for injured workers in Asian countries where work injury management policies are not yet established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…psychoeducation. Other interventions more generally reported the use of psychological and/or behavioural principles (27.5% of studies) (Becker, Angerer, Weber, & Muller, 2020 ; Beemster, van Bennekom, van Velzen, Frings-Dresen, & Reneman, 2020 ; Bergstrom, Bergstrom, Hagberg, Bodin, & Jensen, 2010 ; Bramberg, Bergstrom, Jensen, Hagberg, & Kwak, 2017 ; Brendbekken et al, 2017 ; Brendbekken, Vaktskjold, Harris, & Tangen, 2018 ; Brox et al, 2010 ; Caby et al, 2016 ; Hammond et al, 2017 ; Hampel & Tlach, 2015 ; Hardison & Roll, 2017 ; Hartfiel et al, 2017 ; Hutting et al, 2015 ; Law et al, 2016 ; Lebon, Rongières, Apredoaei, & Delclaux, 2017 ; Lindholdt et al, 2017 ; McCubbin et al, 2014 ; Sandsjo et al, 2010 ; Sullivan & Simon, 2012 ; Sullivan & Adams, 2010 ; Sullivan, Adams, & Ellis, 2012 ; Tan et al, 2016 ; van Vilsteren et al, 2017a ; van Vilsteren et al, 2017b ; Westman et al, 2010 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…psychoeducation. Other interventions more generally reported the use of psychological and/or behavioural principles (27.5% of studies) (Becker, Angerer, Weber, & Muller, 2020 ; Beemster, van Bennekom, van Velzen, Frings-Dresen, & Reneman, 2020 ; Bergstrom, Bergstrom, Hagberg, Bodin, & Jensen, 2010 ; Bramberg, Bergstrom, Jensen, Hagberg, & Kwak, 2017 ; Brendbekken et al, 2017 ; Brendbekken, Vaktskjold, Harris, & Tangen, 2018 ; Brox et al, 2010 ; Caby et al, 2016 ; Hammond et al, 2017 ; Hampel & Tlach, 2015 ; Hardison & Roll, 2017 ; Hartfiel et al, 2017 ; Hutting et al, 2015 ; Law et al, 2016 ; Lebon, Rongières, Apredoaei, & Delclaux, 2017 ; Lindholdt et al, 2017 ; McCubbin et al, 2014 ; Sandsjo et al, 2010 ; Sullivan & Simon, 2012 ; Sullivan & Adams, 2010 ; Sullivan, Adams, & Ellis, 2012 ; Tan et al, 2016 ; van Vilsteren et al, 2017a ; van Vilsteren et al, 2017b ; Westman et al, 2010 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…General health outcomes were also common ( Table 3 ). These were measured, for example, using health-related quality of life measures, such as the SF-36 (Angst et al, 2014 ; Bethge et al, 2011 ; Calner et al, 2017 ; Gross et al, 2017 ; Howard et al, 2012 ; Jensen et al, 2011 ; Jensen et al, 2012b ; Knapp et al, 2015 ; Kold et al, 2012 ; McCubbin et al, 2014 ; Mochari-Greenberger et al, 2020 ; Tan et al, 2016 ; Westman et al, 2010 ). Table 3 also indicates that some outcomes were less commonly measured.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were nine studies that reported on RTW as the number of days take off, with five that reported on it as a mean with standard deviation. Of these five (48,62,(64)(65)(66), one study (48) measured the outcome at two time points and another (62) reported on two groups of patients. The pooled estimate of effect size was 102.3 (95% CI 29.7,174.9) (I 2 = 99.8%); i.e., participants in the included studies took a mean of 102.3 days or around 3.5 months postdischarge to return to work.…”
Section: B Sick Leaves or Days Offmentioning
confidence: 99%